PENGARUH PEMASARAN DIGITAL, WORD OF MOUTH, DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT KUNJUNGAN WISATAWAN - Adri Makarim, Ihsan; Pradana, Bayu Ilham (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
Covid-19 has had an impact on the tourism industry. One of these impacts is that tourist arrivals are decreasing every year. The purpose of this research is to identify and analyze the effects of digital marketing, word of mouth, and online customer review on tourist’s intention to visit Labuan Bajo. The sample of this research was selected using non probability sampling method and purposive sampling technique from a population of individuals living in Tangerang Selatan City who have visited Labuan Bajo, resulting in 115 respondents. The data was acquired from questionnaires, library research, and web browsing and was analyzed using regression analysis. The result showed that digital marketing positively affects tourist’s visit intention. Word of mouth positively influences tourist’s visit intention, and that online customer review positively impacts the tourist’s visit intention.